Improving Cancer Detection and Treatment by pH‐Sensitive Peptide Nanoparticle Drug Delivery Platform: Pharmacokinetics, Toxicity, and Immunogenicity Profile. Issue 3 (2nd March 2022) - Choi, Hoon; Cao, Jianbo; Qiao, Hui; Chen, I-Wei; Zhou, Rong
Abstract : Cancer Detection In article number 2100081, I‐Wei Chen, Rong Zhou, and co‐workers demonstrate that a peptide‐based nanodelivery platform made of pH‐sensitive peptides (blue, turning red when protonated in low pH) and decorated by PEG (yellow) can be used to formulate poorly water‐soluble small molecules to improve cancer diagnosis and treatment. The pH‐sensitive nanoparticles, stable in blood, self‐dissolve in a mildly acidic extracellular space of the tumor, thereby releasing encapsulated molecular drug cargos (silver spheres) near tumor cells.